2021
DOI: 10.1093/rheumatology/keab049
|View full text |Cite
|
Sign up to set email alerts
|

Association between environmental air pollution and rheumatoid arthritis flares

Abstract: Objectives Environmental air pollution has been linked to the pathogenesis of Rheumatoid Arthritis (RA). Nevertheless, evidence linking higher concentrations of air pollutants with the risk of RA reactivations is missing. The objective of the present study was to determine the association between RA flares and air pollution. Methods We collected longitudinal data of patients affected by RA and of the daily concentration of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 28 publications
2
38
1
Order By: Relevance
“…This latter study, as well as our results, provided very small variations in the outcome measures (i.e., disease activity), which, even if statistically significant, did not reach the minimal clinically important difference [22]. Finally, due to the differences in study design (crosssectional vs. longitudinal case-crossover study) and in the period of air pollution exposure before the clinical assessment (seven days "short-term" vs. 30-day and 60-day mediumterm), this study is not comparable with the other recent Italian study [18].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This latter study, as well as our results, provided very small variations in the outcome measures (i.e., disease activity), which, even if statistically significant, did not reach the minimal clinically important difference [22]. Finally, due to the differences in study design (crosssectional vs. longitudinal case-crossover study) and in the period of air pollution exposure before the clinical assessment (seven days "short-term" vs. 30-day and 60-day mediumterm), this study is not comparable with the other recent Italian study [18].…”
Section: Discussioncontrasting
confidence: 70%
“…Another one was conducted in China (Hefei region): the exposure to a high concentration of PM 2.5 and NO 2 was related to hospital readmission within one year after the last discharge in RA patients [17]. Recently, a longitudinal study in the Veneto region (Italy) reported a significant association between disease reactivation and medium-term air pollution exposure (30-days and 60-days before the assessment) [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the latest research studies that has been published is a case-crossover study (which assessed a potential association between air pollutants in the Verona area and RA evolution) in 888 RA patients, showed that air pollution is linked to high C-reactive protein levels (CRP), to the severity of RA illness and its reactivations due to a poor response to biological therapies [ 74 ].…”
Section: Pathophysiology Of Ramentioning
confidence: 99%
“…This is particularly true regarding the pathogenesis of rheumatoid arthritis (RA) (4). In addition, our group has recently demonstrated that exposure to air pollution, even at low exposure thresholds, is strictly associated with RA reactivations (5). Carbon fossil combustion contains a mixture of carbon monoxide (CO), nitric oxide (NO), nitric dioxide (NO 2 ), oxides of nitrogen (NO x ), particulate matter with a diameter of 10 μm or 2.5 μm (PM10 and PM2.5, respectively) or less, and ozone (O 3 ).…”
Section: Introductionmentioning
confidence: 99%